1997
DOI: 10.1063/1.363904
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization and crystallization in high-dose Zn+-implanted silicon

Abstract: The nature of amorphization and crystallization of Si brought about by 50 keV Zn ion implantation within the dose range 2×1017–1×1018 cm−2 is studied. The structures are evaluated in the as-implanted state by transmission electron microscopy, transmission electron diffraction, reflection high-energy electron diffraction, selected-area electron diffraction, x-ray energy-dispersive analysis, and Rutherford backscattering spectrometry. It is found that, contrary to the theoretical predictions, the Zn concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…High zinc diffusion mobility facilitates its active redistribu tion in the implanted layer region. Similar behavioral features of zinc were observed in [7], where implanta tion and annealing were performed under almost the same conditions. On the zinc concentration distribu tion profile (Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…High zinc diffusion mobility facilitates its active redistribu tion in the implanted layer region. Similar behavioral features of zinc were observed in [7], where implanta tion and annealing were performed under almost the same conditions. On the zinc concentration distribu tion profile (Fig.…”
Section: Resultssupporting
confidence: 67%
“…That is why studies of the microstructure and properties of the implanted material during technologi cal treatment are of special importance. Metal ion implantation into semiconductors could result in the formation of metallic precipitates in the implanted layer during implantation [6], as also during subsequent annealing [7] at its different stages. As was established during the implantation of high zinc doses into silicon, nanoparticles of Zn and ZnO with hexagonal structures could form precipitates during the implantation process at room temperature [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently the microstructure of 50 keV, high{dose Zn + implanted Si was studied by TEM in di raction contrast and complementary information on the nature of the implantation induced damaged structures was obtained by x{ray energy dispersive analysis (EDAX) and re ection high energy electron di raction (RHEED). The e ects of sample heating, sputtering and di usion as well as the evolution of the Zn concentration pro les as evaluated by Rutherford backscattering spectrometry (RBS) were taken into account, see 8,9]. The present study is a sequel to this work and, by using HRTEM, sheds new light on the microstructure of the Zn + implanted Si under conditions favourable for IBIC and IBIA.…”
Section: Sample Preparation and Experimental Techniques For Structura...mentioning
confidence: 97%
“…Depending mainly on the mobility and solubility of the implanted species, precipitation can, indeed, occur either during the implantation or the subsequent annealing stage [4]. Regarding high-dose Zn and Bi implantation in Si, it has been demonstrated that nano-scale hexagonal Zn and Bi inclusions can be precipitated directly during implantation at room temperature [5,6], and this is mainly attributed to their low solubility in Si.…”
Section: Introductionmentioning
confidence: 99%